2015
DOI: 10.7752/jpes.2015.02027
|View full text |Cite
|
Sign up to set email alerts
|

Untitled

Abstract: Abstract:The aim is to summarize the impact results of the application of an individual approach on the level of special efficiency; to reveal the influence of an individual approach on the functional state of the sportsmen. Materials: There were 23 qualified basketball players, aged 20-22, involved in the research. Results: We have developed the theoretical conception of individualization of the training process. This concept lies in showing the leading factors in the individual structure of sportsmen' profic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
30
0
2

Year Published

2015
2015
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 45 publications
(34 citation statements)
references
References 2 publications
2
30
0
2
Order By: Relevance
“…Game kinds of sports are an example of such means. Basketball is one of them [1,39,47]. Basketball sets high requirements to functional fitness.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Game kinds of sports are an example of such means. Basketball is one of them [1,39,47]. Basketball sets high requirements to functional fitness.…”
Section: Introductionmentioning
confidence: 99%
“…In this connection application of informative and effective methods of control over organism's functional state acquires great importance. Such approach is required for adequate regulation of physical loads depending on human individual features [23,35,37,44,47]. It should be noted that determination of adults' and children's reactions to physical load by subjective feelings as well as their physiological parameters becomes very important [8].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The analysis of literary data (Arziutov, G., Iermakov, S., Bartik, P., Nosko, M., & Cynarski, W. J., 2016;Boichuk, R., Iermakov, S., & Nosko, M., 2017;Kriventsova, I., Iermakov, S., Bartik, P., Nosko, M., & Cynarski, W. J., 2017;Nosko, M., Razumeyko, N., Iermakov, S., & Yermakova, T., 2016;Osipov, A. Y., Kudryavtsev, M. D., Iermakov, S. S., & Jagiełło, W., 2017) showed that most authors in determining the basic principles of constructing a training process one of the main consider the principle of combining team training and individualization. At the same time, if cyclic and gaming sports already have some work on specific recommendations for the construction of a training process for each team (Pomeshchikova, I., Iermakov, S., Bartik, P., Shevchenko, O., Nosko, M., Yermakova, T., & Nosko, Y., 2016;Zhanneta, K., Irina, S., Tatyana, B., Olena, R., Olena, L., & Anna, I., 2015), then sports aerobics is just beginning to develop the theoretical, methodological and organizational foundations of the unity of team and individual approach to the training process of athletes. In this regard, our work is a new direction in which the principle of unity of command and individualization of the preparation of aerobists is transformed into a system that has its structure, algorithms, mathematical apparatus.…”
Section: Discussionmentioning
confidence: 99%
“…That is why medical-social provisioning of disabled people is so important. In this case inclusive educational medium is an optimal form of ensuring disabled youth with conditions for self expression, self-perfection, self-creation; for realization of equal rights and opportunities, formation of sense of personal significance and usefulness (Makarova, 2012;Sobyanin, & Scherbin, 2012;Zhanneta, K., Irina, S., Tatyana, B., et al, 2015). Less active people, who do not practice recreational or sport functioning, are also less active under everyday loads and in free time (Drygas, Sakłak, Kwaåniewska, 2013;Gorelov, Obvintsev, & Kondakov, 2014;Kozina, 2015;Kozina, Iermakov, Kuzmin, et al, 2016).…”
Section: Introductionmentioning
confidence: 99%